2010
DOI: 10.1007/s10147-010-0061-x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based guidelines for treatment of cervical cancer in Japan: Japan Society of Gynecologic Oncology (JSGO) 2007 edition

Abstract: Clinical practice guidelines for gynecologic cancers have been published by the National Comprehensive Cancer Network and the National Cancer Institute. Whereas these guidelines form the basis for the standard of care for gynecologic malignancies in the United States, it has proven difficult to institute them in Japan due to differences in patient characteristics, health-care delivery systems, and insurance programs. Therefore, evidence-based guidelines for treating cervical cancer specifically in Japan have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 2 publications
0
52
0
Order By: Relevance
“…1 However, the Japanese treatment guideline for cervical cancer published in 2007 gave CCRT a grade B recommendation. 2 The guideline stated that clinical questions remained to be answered before CCRT could be designated as a standard therapy with a grade A recommendation in Japan. 2 The Gynecologic Oncology Group (GOG) protocol 120 demonstrated that a weekly dose of 40 mg/m 2 of intravenous cisplatin for 6 weeks was equally efficacious and less toxic compared with a combination regimen of cisplatin and 5-fluorouracil for 2 cycles of CCRT.…”
mentioning
confidence: 99%
“…1 However, the Japanese treatment guideline for cervical cancer published in 2007 gave CCRT a grade B recommendation. 2 The guideline stated that clinical questions remained to be answered before CCRT could be designated as a standard therapy with a grade A recommendation in Japan. 2 The Gynecologic Oncology Group (GOG) protocol 120 demonstrated that a weekly dose of 40 mg/m 2 of intravenous cisplatin for 6 weeks was equally efficacious and less toxic compared with a combination regimen of cisplatin and 5-fluorouracil for 2 cycles of CCRT.…”
mentioning
confidence: 99%
“…The recommended surgical treatment for women with stage Ib2-Ib1 cervical cancer is a radical hysterectomy and bilateral pelvic lymphadenectomy [9]; however, many women diagnosed with cervical cancer have not completed their childbearing. There is increasing evidence in the literature that radical trachelectomy is a viable option for young women with cervical cancer who wish to preserve their fertility [10,11]; however, the eligibility for this procedure is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…If residual disease persists 2 months after radiotherapy, extrafascial hysterectomy can be a valid option. (Chuang et al, 2016, Nagase et al, 2010, Cetina et al, 2013, Kokka et al, 2015, Censo Nacional de Población, 2010). …”
Section: Recommendations Of Management Of Cervical Cancer In Argentinamentioning
confidence: 99%